INVESTIGATING HEALTHBELIEFSANDINTENTIONFORSMOKING CESSATIONBASEDONTHEHEALTHBELIEFMODEL - Christy Ofeelia, Meyndi; Manalu, S. Rouli; Luqman, Yanuar (Interaksi Online, 2024)
This study investigates the relationship between perceived health belief factors and the intention for smoking cessation in utilizing the Health Belief Model (HBM) as the theoretical framework. HBM identifies health components— Perceived Susceptibility, Perceived Severity, Self-Efficacy, Perceived Benefits, Perceived Barriers, and Cues to Action—that influences an individual's decision-making to engage with a health-promoting behavior, such as smoking cessation. The research objective focuses on determining significant correlations between HBM determinants towards the active smokers' intentions in quitting. A cross-sectional survey examined a sample of 200 smokers classified between ages 18-60 years residing in Indonesia, which was selected through a non-probability sampling to participate in the questionnaire. Kendall's Tau-B correlation coefficient was employed within the study to analyze the correlations between the health belief components towards the intention to quit smoking. Results showed that Perceived Susceptibility (P=.000), Perceived Severity (P=.000), Self-Efficacy (P= .000), Perceived Benefits (P=.000), and Cues to Action (P=.014) had significant positive correlations with the Intention for Smoking Cessation. Research findings emphasized the importance in addressing smokers’ beliefs regarding the health consequences and risks, self-efficacy in quitting, and perception towards challenges within smoking cessation as a health promoting behavior. Tailoring public health awareness and prevention programs with deeper insights to the beliefs and perceptions among smokers is suggested to reduce perceived barriers and enhance cues to action as a more effective strategy in promoting smoking cessation